The Vulnerability Typology: Developing a Biopsychosocial-Sexual Understanding of Men With Sexual Interests in Children - Stewart, Hannah Ruth (Sexual offending, 2025)
The goal of the current study was to better understand biopsychosocial factors related to men with sexual interests in children (MSICs) who have no criminal history of sexual offending to clarify heterogeneity and potential targets for preventative intervention for persons who are at risk of sexual offending. Using online recruitment methods, self-report data on biopsychosocial-sexual factors was collected from community men reporting paraphilic and atypical sexual interests, including men with sexual interests in children (n = 609; Mage = 29.7 years) and a comparison group with other paraphilias (n = 224; Mage = 35.3 years). Data were used to develop a biopsychosocial-sexual typology of community men with pedohebephilic interests with no reported offence history. Latent cluster analysis identified three groups differentiated by relative endorsement of biopsychosocial vulnerability characteristics. Comparisons between profiles indicated a generally unimpaired profile (i.e., Low Vulnerability) relative to a group with intermediate vulnerabilities (i.e., Moderate Vulnerability) and a group with significant impairment across most assessed constructs (i.e., High Vulnerability). Results inform areas of need for secondary prevention among community MSICs with no historical justice system contact related to their sexual interests in children. Consistent with Risk-Need-Responsivity Model, this research suggests that intensity and dosage of preventative intervention for MSICs should match level of vulnerability.